Lactate threshold changes in soccer players during the preparation period - Jastrzebski, Z.; Dargiewicz, R.; Ignatiuk, W.; Radziminski, L.; Rompa, P.; Konieczna, A. (Baltic Journal of Health and Physical Activity, 2011)
Background: The aim of the study was to assess the anaerobic threshold (lactate threshold LT) changes during winter and summer preparation period in soccer premier league and first division players. It was assumed that the index value varies depending on the stage of a one-year training cycle.